PENINGKATAN PRODUKSI DAN NILAI NUTRISI HIJAUAN Pueraria phaseoloides OLEH PEMUPUKAN FOSFOR DALAM SUSPENSI FERMENTASI Acetobacter-Saccharomyces - Dwi Retno Lukiwati; Novik Nurhidayat; C. Anggit Hatmaji Wibowo; J. Bambang Tri Nurdewanto (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2005)
Puero (Pueraria phaseoloides) which is important legume as protein and mineral source is sensitive to the phosphorus deficiency. However, because of the high cost of superphosphate (SP), the focus is now on rock phosphate fertilizer (RP). Rock phosphate fertilizer, as one of the natural P sources, is relatively cheaper than SP but it slowly available to plants. Fermentation solution of Acetobacter-Saccharomyces (FSAS) maybe a promising technique to overcome this problem. A greenhouse experiment was conducted during 8 weeks on acid latosolic soil and low phosphorus availability. A completely randomized design with 5 treatments, and 4 replicates was used. The treatments were contro, RP, SP, RP+FSAS, and SP+FSAS. Phosphorus fertilizer level was 200 kg P2O5 ha-1 (2.22 g RP per pot or 1.67 g SP per pot). Puero was cut and measured for dry matter (DM), crude protein content (CP), S and Se content on 8 weeks after planting. All data were analyzed by the GLM procedure of SAS. Significant differences among the treatments were calculated by DMRT. The results show that SP+FSAS increased DM production, CP and Se content significantly higher compared to SP (P<0.05). However, RP+FSAS resulted DM production, CP and S content of puero did not difference compared to SP, but Se content significantly higher (P<0.05). Phosphorus fertilization (RP, SP) + FSAS could increase Se content of puero. No differences in DM production, CP and S content were found between RP+FSAS compared to SP fertilization.